Natural Polymer-Cell Bioconstructs for Bone Tissue Engineering - Titorencu, Irina; Georgiana Albu, Madalina; Nemecz, Miruna; V. Jinga, Victor (Current Stem Cell Research & Therapy, 2017)
The major goal of bone tissue engineering is to develop bioconstructs which substitute the functionality of damaged natural bone structures as much as possible if critical-sized defects occur. Scaffolds that mimic the structure and composition of bone tissue and cells play a pivotal role in bone tissue engineering applications. First, composition, properties and in vivo synthesis of bone tissue are presented for the understanding of bone formation. Second, potential sources of osteoprogenitor cells have been investigated for their capacity to induce bone repair and regeneration. Third, taking into account that the main property to qualify one scaffold as a future bioconstruct for bone tissue engineering is the biocompatibility, the assessments which prove it are reviewed in this paper. Forth, various types of natural polymer- based scaffolds consisting in proteins, polysaccharides, minerals, growth factors etc, are discussed, and interaction between scaffolds and cells which proved bone tissue engineering concept are highlighted. Finally, the future perspectives of natural polymer-based scaffolds for bone tissue engineering are considered.
Keywords: scaffolds